Exact Solutions of the Benney–Luke Equation via (1/G')- Expansion Method - Durur, Hülya; Yokuş, Asıf (My University, 2021)
In this study, the(1/ ) G? -expansion method was implemented to solve the Benney–Luke (BL) equation. Exactsolutions of the BL equation were obtained via this method. The solutions obtained from the BL equation were inhyperbolic form. 3D, 2D and contour graphs of obtained solutions are presented. Results show that the(1/ ) G? - expansion method provides an efficient and straightforward mathematical instrument for finding solutions ofnonlinear evolution equations (NLEEs).
Keywords: Matematik; Fizik; Matematik